Pengaruh Proses Pengeringan dan Campuran Briket Antrasit dengan Biomassa Serbuk Gergaji Kayu Terhadap Kadar Abu dan Volatile Matter - Fadhian, Muhammad FIlo; Wahyudie, Illham Ary; Yuliyanto, Yuliyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The Indonesian government recognizes the importance of transitioning away from dependence on fossil fuels. Briquettes are becoming the most popular option for overcoming fossil fuel dependence. This study examines the effect of the drying process and variation of anthracite mixture with wood sawdust on ash content and volatile matter in briquettes. The study used a factorial method with three process variables: water and molasses fractions, temperature, and holding time. The results showed that the highest ash content was obtained in briquettes with a water and molasses fraction of 1:1, while the lowest ash content was at a fraction of 2:1. The temperature and drying time also affected the ash content, where lower temperature and longer drying time resulted in lower ash content. Regarding volatile matter, briquettes with a drying temperature of 120°C and a drying time of 60 minutes produced the lowest volatile matter content. This study concludes that combining the drying process and the right mix of ingredients can improve the quality of briquettes, although the results obtained have not met the established SNI standards.